Coherent banking capital and optimal credit portfolio structure - Wolfgang Breuer; Marc Gürtler (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2006)
Coherent measures of a bank's whole risk capital imply a structure of a bank's optimal credit portfolio that is independent of its deposits and the expected deposit rate, of expected bankruptcy costs and of expected costs of regulatory capital.
Keywords: G21; G28; 330; Basel II; Regulatory Capital; Coherent Risk Capital; Separation